NEW EVIDENCE FOR SUPRA-SUBDUCTION ZONE OPHIOLITES IN THE VARDAR ZONE OF NORTHERN GREECE: IMPLICATIONS FOR THE TECTONO-MAGMATIC EVOLUTION OF THE VARDAR OCEANIC BASIN - Saccani, Emilio; Photiades, Adonis; Santato, Alessandro; Zeda, Ottavia (Ofioliti, 2008)
The Vermion Massif (northern Greece) is located across the boundary between the Pelagonian and Vardar Zones and includes several tectonic units bearing ophiolitic rocks, which represent remnants of the oceanic lithosphere formed in the Neotethyan Vardar Ocean, between the Pelagonian and the Serbo- Macedonian continental realms. This massif consists of tectonic units belonging to the Pelagonian Domain, which are tectonically overlain by units associated with the Almopias sub-Zone (Vardar Zone). Ophiolitic rocks consist of mantle harzburgites and ophiolitic mélanges. The ophiolitic mélanges incorporate rocks exhibiting a wide range of composition, including various intrusive rocks and volcanic rocks ranging from basalts, basaltic andesites, andesites, dacites, to rhyolites.Incompatible elements and rare earth elements analyses indicate that a number of different rock-types formed in distinct tectonic settings can be identified. Mantle harzburgites have a very depleted nature and represent portions of the supra-subduction (SSZ) mantle developed in an intra-oceanic arc setting. The mélanges units include six rock types variably distributed in the Pelagonian and Almopias Units. They are: (1) calc-alkaline rocks with marked depletion in Nb, Ta Ti and enrichment in LREE, Th; (2) LREE-depleted N-MORB; (3) LREE-enriched E-MORB; (4) alkaline within-plate basalts showing marked enrichments in Th, Ta, Nb, LREE; (5) low-Ti island arc tholeiites featuring depletion in HFSE; and (6) very-low-Ti boninites characterized by strong depletion in HSFE and REE. Previous interpretations have referred the Vardar ophiolites to a MORB-type oceanic setting and to a MORB-type backarc setting; however, the widespread occurrence of SSZ ophiolites has never been documented in the Vardar Zone before and is particularly important as it testifies for the existence of an intra-oceanic arc basin in the Vardar oceanic domain.The results presented in this paper compared with literature data on other magmatic rocks within the Vardar Zone suggest that the opening and closure of the Vardar Ocean record several distinct accretion events in this basin, that is oceanic crust generation at mid-ocean ridge, alkaline seamounts in the oceanic domain and SSZ setting, as well as two accretion events in the western realm of the Serbo-Macedonian continent, that is volcanic arc and backarc settings.Based on the comparison between the modern west Pacific subduction system and the results from this study a new model for a multistage tectono-magmatic evolution of the Vardar Ocean is proposed.